REGULASI EMOSI PESERTA DIDIK SMA DAN SMK DITINJAU DARI JENIS KELAMIN DAN JENIS SEKOLAH - Muhammad Ridho Nuruddin; Retno Tri Hariastuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Emotion regulation is an important ability for adolescents in dealing with various pressures and changes during their developmental period, considering that poor emotional management can trigger negative behaviors such as bullying and violence in the school environment. This study aims to determine differences in students’ emotion regulation based on gender and school type. The study employed a quantitative approach with a comparative design. The subjects consisted of 181 senior high school and vocational high school students in Lakarsantri District, including 83 male students and 98 female students, selected using a saturated sampling technique. The research instrument was an emotion regulation scale based on the aspects proposed by Gratz and Roemer, consisting of 38 items with a Cronbach’s Alpha reliability coefficient of 0.865. Data were analyzed using the Two Way ANOVA technique after fulfilling the assumptions of normality and homogeneity. The results showed no significant differences in emotion regulation based on gender (Sig. = 0.470), school type (Sig. = 0.412), or the interaction between both variables (Sig. = 0.920). The R Squared value of 0.006 indicates that emotion regulation is more strongly influenced by factors other than gender and school type. These findings suggest that guidance and counseling services in schools should focus on developing students’ emotion regulation skills comprehensively through preventive services and strengthening socio emotional skills for all students. ABSTRAK Regulasi emosi merupakan kemampuan penting bagi remaja dalam menghadapi berbagai tekanan dan perubahan yang terjadi selama masa perkembangan, mengingat lemahnya pengelolaan emosi dapat memicu perilaku negatif seperti bullying dan kekerasan di lingkungan sekolah. Penelitian ini bertujuan untuk mengetahui perbedaan regulasi emosi peserta didik ditinjau dari jenis kelamin dan jenis sekolah. Penelitian menggunakan pendekatan kuantitatif dengan desain komparatif. Subjek penelitian berjumlah 181 peserta didik SMA dan SMK di Kecamatan Lakarsantri yang terdiri atas 83 siswa laki-laki dan 98 siswa perempuan, dengan teknik sampling jenuh. Instrumen penelitian berupa skala regulasi emosi berdasarkan aspek Gratz dan Roemer yang terdiri atas 38 item dengan reliabilitas Cronbach’s Alpha sebesar 0,865. Data dianalisis menggunakan teknik Two-Way ANOVA setelah memenuhi uji asumsi normalitas dan homogenitas. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan regulasi emosi berdasarkan jenis kelamin (Sig. = 0,470), jenis sekolah (Sig. = 0,412), maupun interaksi keduanya (Sig. = 0,920). Nilai R Squared sebesar 0,006 menunjukkan bahwa regulasi emosi lebih banyak dipengaruhi oleh faktor lain di luar jenis kelamin dan jenis sekolah. Temuan ini mengindikasikan bahwa layanan bimbingan dan konseling di sekolah perlu difokuskan pada pengembangan keterampilan regulasi emosi secara menyeluruh melalui layanan preventif dan penguatan keterampilan sosial emosional bagi seluruh peserta didik.